PENGARUH RISIKO INFLASI, RISIKO KREDIT (NPL) DAN RISIKO LIKUIDITAS (LDR) TERHADAP PROFITABILITAS (ROA) DI MASA PANDEMI COVID-19 - Nur Rantika Octavia; Gusgana Suria Manda (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
The purpose of this study was to find out how big the Influence of Inflation Risk, Credit Risk (NPL) and Liquidity Risk (LDR) on Profitability (ROA) During the Covid-19 Pandemic Period in State-Owned Banks for the 2018-2020 Period. The method used was descriptive method with a quantitative approach assisted by the SPSS program, namely through classical assumption test analysis, multiple linear regression analysis and hypothesis testing using simultaneous test (F test), partial test (t test), and coefficient of determination test (R2). . The data used in this study was secondary data where the data collection was indirectly so that it uses existing data information. This study uses the population at state-owned banks for the 2018-2020 period using the Saturated Sampling technique because the sampling technique takes all the population to be used as samples. Based on the results of the t-test partially Credit Risk (NPL) has a significant effect on Profitability (ROA), while Inflation Risk and Liquidity Risk (LDR) have no significant effect on Profitability (ROA). From the results of Adjusted R Aquare shows that simultaneously Profitability (ROA) was influenced by Inflation, Credit Risk (NPL), and Liquidity Risk (LDR) by 62%, while the remaining 38% is influenced by other factors.